The first wave of the transvestite scene in Brazil: The centrality of the "transvestite body” (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The interdisciplinary essay understands the “transvestite scene” in Brazil as transvestite aesthetics, professional practice of transvestism, away from identity issues and proposes the division of this scene into four waves, phases, movements. Based on studies on Theatre, History and Queer Theory, the authors focus on the first wave from where they extract relevant aesthetic characteristics that will reflect, above all, in the second wave.
Keywords: Transvestite scene; Brazilian theater; Aymond; Ivaná